The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1007/s00256-009-0719-5
|View full text |Cite
|
Sign up to set email alerts
|

Intra-observer and interobserver reliability of the ‘Pico’ computed tomography method for quantification of glenoid bone defect in anterior shoulder instability

Abstract: Measurement of glenoid bone defect in anterior shoulder instability can be assessed with the Pico method, based on en face images of the glenoid processed in MPR, with a very good intra-observer and interobserver reliability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
0
9

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(73 citation statements)
references
References 35 publications
0
64
0
9
Order By: Relevance
“…The same glenoid parameters were used in Magarelli et al's [42] research. They analysed inter-and intra-observer reliability of the method used for anterior gleno-humeral instability assessment based only on 2D-CT images.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The same glenoid parameters were used in Magarelli et al's [42] research. They analysed inter-and intra-observer reliability of the method used for anterior gleno-humeral instability assessment based only on 2D-CT images.…”
Section: Discussionmentioning
confidence: 99%
“…They analysed inter-and intra-observer reliability of the method used for anterior gleno-humeral instability assessment based only on 2D-CT images. Magarelli et al [42] showed that measurement of glenoid bone defect in anterior shoulder instability could be assessed based on 2D-CT images, with a very good intra-observer and inter-observer reliability. In turn, Sugaya and co-workers [41] concluded that 2D-CT is not adequate for quantification and surgical planning because it did not show details of the glenoid rim.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors have concluded that the PICO measurement technique reliably produces an accurate and reliable measure of glenoid bone loss in shoulder instability [29][30][31] . The PICO method involves obtaining en-face 3D views of both the affected and normal glenoid.…”
Section: Glenoid Bone Lossmentioning
confidence: 99%
“…The loss of the anterior sclerotic glenoid line (SGL) in neutral rotation radiographs is currently widely used to detect anterior glenoid bone loss [20]. CT-scan measurement methods of anterior glenoid bone loss have been recently developed [4,17,24,29]. Gerber et al [15] also published a simple method of measuring antero-inferior glenoid bone loss on 2D CT-scans and entitled it the X index.…”
Section: Introductionmentioning
confidence: 98%